If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = x + -15 Reorder the terms: -3 = -15 + x Solving -3 = -15 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + -1x = -15 + x + -1x Combine like terms: x + -1x = 0 -3 + -1x = -15 + 0 -3 + -1x = -15 Add '3' to each side of the equation. -3 + 3 + -1x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -15 + 3 -1x = -15 + 3 Combine like terms: -15 + 3 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t | | 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 | | 36x=-8x | | 25b^4-211b^2+3024=0 | | 3(n-2)=3(2n+4) | | -10+2j=-2 | | 6x(4+3)= | | X^72/8x^4 | | -5(x-1)=-10x+20 | | B^0/ba^5 | | (9)(10)-(3)(4)= | | 3w+6+4w= | | 5x+6y=67 | | 7x(1/3xN)-4=10 |